2017
DOI: 10.1007/s00277-017-3090-y
|View full text |Cite
|
Sign up to set email alerts
|

Widening the spectrum of deletions and molecular mechanisms underlying alpha-thalassemia

Abstract: Inherited deletions of α-globin genes and/or their upstream regulatory elements (MCSs) give rise to α-thalassemia, an autosomal recessive microcytic hypochromic anemia. In this study, multiplex ligation-dependent probe amplification performed with commercial and synthetic engineered probes, Gap-PCR, and DNA sequencing were used to characterize lesions in the sub-telomeric region of the short arm of chromosome 16, possibly explaining the α-thalassemia/HbH disease phenotype in ten patients. We have found six dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Approximately 30‐70 kb upstream of the α‐globin gene cluster, four highly conserved elements (MCS‐R1 to 4), corresponding to erythroid‐specific DNase I hypersensitive sites (HS‐48, HS‐40, HS‐33, HS‐10, respectively), act as long‐range regulatory elements of the α‐like globin genes 3 . There have been many reports which found that deletions of these regulatory elements lead to α‐thalassemia phenotypes because of severe downregulation of the α‐globin gene expression in the affected chromosome 4‐8 . Interestingly, in almost all reported cases, the MCS‐R2 alone, or along with other MCS‐R elements, is removed.…”
Section: Age Rbc Hb MCV Mch Hba Hba2 Hbf Hbcs Hbh Hbbarts Hbh Bodies α Genotype β Genotypea (Y) (×1012) (G/dl) (Fl) (Pg) (%) (%) (%) (%) mentioning
confidence: 99%
“…Approximately 30‐70 kb upstream of the α‐globin gene cluster, four highly conserved elements (MCS‐R1 to 4), corresponding to erythroid‐specific DNase I hypersensitive sites (HS‐48, HS‐40, HS‐33, HS‐10, respectively), act as long‐range regulatory elements of the α‐like globin genes 3 . There have been many reports which found that deletions of these regulatory elements lead to α‐thalassemia phenotypes because of severe downregulation of the α‐globin gene expression in the affected chromosome 4‐8 . Interestingly, in almost all reported cases, the MCS‐R2 alone, or along with other MCS‐R elements, is removed.…”
Section: Age Rbc Hb MCV Mch Hba Hba2 Hbf Hbcs Hbh Hbbarts Hbh Bodies α Genotype β Genotypea (Y) (×1012) (G/dl) (Fl) (Pg) (%) (%) (%) (%) mentioning
confidence: 99%
“…Diagnosing and detecting thalassemia and other hemoglobinopathies begin with relevant family history, laboratory screening, and invasive prenatal screening via obtaining amniocentesis and chorionic villus sampling when the parents are at high risk for hemoglobinopathies. Moreover, new molecular genetic technologies to map and detect mutation and deletion by sequencing analysis prenatally [10,12,13]. Most of these technologies include PCR screening for mutations, electrophoresis, high-performance liquid chromatography (HPLC), and DNA test [10,14].…”
Section: Diagnosis and Subtypes Of Thalassemiamentioning
confidence: 99%
“…Very rarely, the deletion that gives rise to α-thalassemia only affects one distal regulatory region, such as the HS-40, leaving the α-globin genes intact but partially inactivated [ 17 , 23 27 ]. Some of these rare types of deletions that affect the regulatory elements, have also been found in Portuguese individuals, namely the (αα) MM , (αα) ALT , (αα) TI and (αα) CSC [ 22 , 23 , 28 ].…”
Section: Introductionmentioning
confidence: 99%